Is the population of Crotalus durissus (Serpentes, Viperidae) expanding in Brazil? - Duarte, Marcelo Ribeiro (BioMed Central, 2013)
Crotalus durissus are found from Mexico to northern Argentina in a highly disjunct distribution. According to some studies, this species is prone to occupy areas disturbed by human activities and floods comprise a plausible method of dispersal as inferred for some North American rattlesnakes. Based on the literature, it seems plausible that Crotalus durissus expanded their natural distribution in Brazil due to floods, but only in a few municipalities in Rio de Janeiro State. Data entries of Butantan Institute, in São Paulo, Brazil, from 1998 to 2012 show a declining tendency of snakes brought by donors. In addition, research shows no evidence of Crotalus durissus being an expanding species in the Brazilian territory.